COMPARISON OF ISC AND SE ASIA CATALOGS - Lu N.T. (My University, 1999)
The determination of earthquake parameters (t 0, φ, λ, h, M) for the RECSA and ISC catalogs is discussed. It is shown that the epicenter coordinates (latitude and longitude) are similar in the two catalogs. The depth difference is mostly within the range h = 5-10 km; the mean difference in time origin is t = -0.97 s. Relations were found for correlating MSH magnitudes with M(b) and M(s) values.